2022
DOI: 10.3390/ma15207122
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aging Treatment on Microstructural Evolution and Mechanical Properties of the Electron Beam Cold Hearth Melting Ti-6Al-4V Alloy

Abstract: Ti-6Al-4V (Ti64 or TC4) alloy is widely used in the industrial field. However, there have been few studies of the TC4 alloy melted by electron beam cold hearth melting (EBCHM) technology. Aging treatment has a considerable influence on the secondary α-phase in titanium alloys. Therefore, TC4 alloy melted by EBCHM technology was investigated in this study. The effect of different aging times on the microstructural evolution and mechanical properties of titanium alloy sheets was evaluated. The results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…3 demonstrates that as the heat treatment process and ageing period rise, the primary α phase and the grain globulars steadily increase, but the volume fraction of α/α′ phase remains unchanged considerably (Table 2). The morphological characteristic of phases changed noticeably; many secondary α phases precipitated in the matrix seemed to merge together and develop, and some β phases disappeared, according to previous study [39][40][41]. The coarse α phase can be seen in Fig.…”
Section: Discussion Of the Centrifugal Casting For Orthopedic Implant...supporting
confidence: 55%
“…3 demonstrates that as the heat treatment process and ageing period rise, the primary α phase and the grain globulars steadily increase, but the volume fraction of α/α′ phase remains unchanged considerably (Table 2). The morphological characteristic of phases changed noticeably; many secondary α phases precipitated in the matrix seemed to merge together and develop, and some β phases disappeared, according to previous study [39][40][41]. The coarse α phase can be seen in Fig.…”
Section: Discussion Of the Centrifugal Casting For Orthopedic Implant...supporting
confidence: 55%
“…There is a consensus of views [ 7 , 11 , 20 , 30 , 32 , 33 ] that carbon increases the age hardenability of titanium alloys. Yu et al [ 34 ] reported that a slight increase in the content of carbon (from 0.008 to 0.034 wt.%) in the quenched Ti-10V-2Fe-3Al alloy and a decrease in the rate of heating to the aging temperature improves the dispersity of secondary phases formed after quenching and promotes growth in the alloy hardness.…”
Section: Resultsmentioning
confidence: 99%
“…The grain size and nucleation quantity of TC4 alloy are inflluenced by the β heat treatment temperature, and the heat treatment temperature in the α+β region is approximately 100 °C below the phase transition point [30] . The aging process of TC4 alloy involves heating to around 500-600 °C, followed by holding for 4-12 h [31] . Therefore, based on the measured β phase transition point, the two β heat treatment temperatures of 1,050 °C and 1,150 °C were set to study the effect of solution temperature on microstructure and properties.…”
Section: Determination Of Heat Treatment Processmentioning
confidence: 99%